(untitled) (Medicine Today, 2026)
Introduction: Osteoarthritis (OA) is highly debilitating due to pain, stiffness, loss of function, disability and impaired quality of life. Currently, there is no effective treatment for OA because the pathophysiology of OA is poorly understood. To know whether inflammation is associated or not with OA, the aim of the present study was to assess serum interleukin-6 level in grade II-III knee OA. Materials and Methods: Adults with knee pain, radiologically diagnosed with mild to moderate (grade II-III) knee OA, participated in this observational, descriptive, cross-sectional study. X-ray of knee joint of total 61 patients were done and diagnosed as grade II or III knee OA by a competent physiatrist according to the Kellgren-Lawrence (K-L) radiographic grading scale in the department of physical medicine and rehabilitation at BMU from October 2023 to June 2024. Serum Interleukin-6 (IL-6) levels were measured by chemiluminescence immunoassay (CLIA) method at the Snibe Maglumi 2000+ system. Results: In this study, serum IL-6 level was found to be increased in 55 (90.16%) out of 61 patients. However, serum IL-6 level was found within normal range in rest of the 6 (9.84%) patients. Conclusion: Inflammation might be associated with the knee OA. Serum IL-6 level may be used as a biomarker to help the clinicians for diagnosis and target for the anti-inflammatory therapy of knee OA. Medicine Today 2026, Vol.38 (1): 123-128